"Det føles ikke-mandigt på en måde" - Tjørnhøj-Thomsen, Tine (Kvinder, Køn & Forskning, 1999)
The article addresses the theme of "masculinities" from the perspective of infertile men and their partners. It argues that experiences of infertility should be understood as disruption in relation to the body and in relation to the narrative of life that is informed by cultural notions of kinship and gender. These notions are closely connected to a culturally specific story of coming-into-being, which gives symbolic priority to biological procreation and genetic connectedness. Being a real father and a real man depends on procreative abilities. In order to come to terms with infertility, infertile men try to redefine such ideologies of authenticity. The article illustrates how infertile men are confronted by strong cultural associations between fertility, sexuality and masculinity, and how these notions are related to other ideas of masculinity such as independence of the individual, ability to be a provider and a conception of the "intact" body. Finally, the article demonstrates how men and women differ in coping with infertility, childlessness and fertility treatment, and their longings for parenthood. However, gender is not the only difference, which makes a difference in the world of infertile and childless people. The ideas of masculinities unfold through men's relations with other men and through generational differences and similarities.